2017
DOI: 10.1177/2150131917709403
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Expansion Produces Long-Term Impact on Insurance Coverage Rates in Community Health Centers

Abstract: Background It is crucial to understand the impact of the Affordable Care Act (ACA). This study assesses changes in insurance status of patients visiting community health centers (CHCs) comparing states that expanded Medicaid to those that did not. Methods Electronic health record data on 875,571 patients aged 19 to 64 years with ≥ 1 visit between 2012 and 2015 in 412 primary care CHCs in 9 expansion and 4 nonexpansion states. We assessed changes in rates of total, uninsured, Medicaid-insured, and privately i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 9 publications
1
33
0
Order By: Relevance
“…The ACA led to increased access to health care services for patients seen in CHCs. 6,12 This in- . The retrospective cohort of established patients included those who were uninsured at their last visit pre-ACA (2012 to 2013) and gained insurance coverage post-ACA (2014 to 2015).…”
Section: Discussionmentioning
confidence: 95%
“…The ACA led to increased access to health care services for patients seen in CHCs. 6,12 This in- . The retrospective cohort of established patients included those who were uninsured at their last visit pre-ACA (2012 to 2013) and gained insurance coverage post-ACA (2014 to 2015).…”
Section: Discussionmentioning
confidence: 95%
“…Additional funding to support CHCs will be needed for them to continue to provide care for increasing numbers of uninsured patients. Although prior studies have shown that the ACA improved access to health insurance and decreased uninsurance rates, [6][7][8][9][10] none have examined changes in Visits refer to overall ambulatory care use, which includes all billable encounters.…”
Section: Discussionmentioning
confidence: 99%
“…4 The ACA augmented funding for CHCs for 5 years (through 2017), which was renewed in early 2018, allowing them to continue to provide care for the uninsured, assist insured patients with significant out-of-pocket expenses, and provide services not covered by health insurance. 5,6 Post-ACA, CHCs experienced an increase in both Medicaid-paid visits and privately insured visits [6][7][8][9][10] and corresponding decreases in uninsured visits. More than 6 million patients seen at CHCs across the nation, however, remain uninsured.…”
mentioning
confidence: 99%
“…Uninsurance rates among CHC patients decreased dramatically after the ACA, particularly in states that expanded Medicaid eligibility. 9 For example, rates of uninsured visits to CHCs decreased 57% from the period before the ACA to the period after the ACA in expansion states, whereas nonexpansion states saw a 20% decrease; however, Medicaid-insured visits increased by 60% in expansion states and remained unchanged in nonexpansion states. 9 Cancer July 15, 2020…”
Section: Introductionmentioning
confidence: 99%